OBSTACLES IN RENDERING ENGLISH SCIENTIFIC AND TECHNOLOGICAL WRITINGS INTO UZBEK - I.A. Egamberdiyeva,; Sheraliyeva Nozima, (Ustozlar uchun, 2025)
Annotation: This article analyzes the main challenges encountered in translating scientific and technical articles from English into Uzbek. It highlights issues such as terminological accuracy, grammatical equivalence, stylistic features, and contextual consistency. The article also discusses strategies that translators can use to overcome these difficulties, emphasizing the importance of both linguistic and subject matter expertise. The findings provide practical recommendations for improving translation quality in the field of science and technology.